2012
DOI: 10.1016/j.phrs.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Eph receptor–ephrin ligand interaction by tea polyphenols

Abstract: Tea contains a variety of bioactive chemicals, such as catechins and other polyphenols. These compounds are thought to be responsible for the health benefits of tea consumption by affecting the function of many cellular targets, not all of which have been identified. In a high-throughput screen for small molecule antagonists of the EphA4 receptor tyrosine kinase, we identified five tea polyphenols that substantially inhibit EphA4 binding to a synthetic peptide ligand. Further characterization of theaflavin mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…They inhibit ephrin-induced phosphorylation without affecting cell viability or phosphorylation of other receptor tyrosine kinases and, importantly, also inhibit EphA2-dependent retraction of the cell periphery in prostate cancer cells. Moreover, natural compounds such as lithocholic acid (Giorgio et al 2011) and tea polyphenols (Noberini et al 2012a), have also been shown to inhibit ephrin binding to EphA4 and several other Eph receptors at low micromolar concentrations. Some of the polyphenols were shown to inhibit tyrosine phosphorylation, which was affected by mutations within the ligand-binding cavity of EphA4.…”
Section: Eph Receptors and Ephrinsmentioning
confidence: 99%
“…They inhibit ephrin-induced phosphorylation without affecting cell viability or phosphorylation of other receptor tyrosine kinases and, importantly, also inhibit EphA2-dependent retraction of the cell periphery in prostate cancer cells. Moreover, natural compounds such as lithocholic acid (Giorgio et al 2011) and tea polyphenols (Noberini et al 2012a), have also been shown to inhibit ephrin binding to EphA4 and several other Eph receptors at low micromolar concentrations. Some of the polyphenols were shown to inhibit tyrosine phosphorylation, which was affected by mutations within the ligand-binding cavity of EphA4.…”
Section: Eph Receptors and Ephrinsmentioning
confidence: 99%
“…Other than multi-target RTK inhibitor, Noberini et al in Pasquale EB's lab identified two isomeric 2, 5-dimethylpyrrolyl benzoic acid derivatives able to selectively inhibit ephrin binding to EphA4 and EphA2 as well as the function of these receptors in live cells [43]. In fact, this lab has discovered a series of small molecules targeting Eph receptors [44][45][46], which may serve as lead compounds for drug development, as well as targeting agents to deliver drugs or imaging agents to tumors. The antibody-based drugs targeting EphA2 have also been developed, including an antibody-drug conjugate (MEDI-547) composed of a fully human monoclonal antibody against both human and murine EphA2 (1C1) and the tubulin polymerization inhibitor monomethylauristatin F [47] and EA5 [48].…”
Section: Potential Therapeutic Reagents Targeting Ephs/ Ephrins In Lumentioning
confidence: 99%
“…In the case of Eph receptors, a number of small molecule antagonists preferentially targeting EphA2 and EphA4, or a larger subset of Eph receptors, have been identified (29, 3437). More selective peptide inhibitors of interactions between Eph receptors and ephrins have also been identified (28), including a 15 amino acid peptide (TNYL-RAW, amino acid sequence TNYLFSPNGPIARAW) that selectively targets EphB4 by binding to the ephrin-binding pocket of the receptor (38). The shorter peptide TNYL (TNYLFSPNGPIA), which inhibits ephrin-B2 binding to EphB4 with an IC 50 value of ~150 µM, was identified by using phage display.…”
Section: Introductionmentioning
confidence: 99%
“…The shorter peptide TNYL (TNYLFSPNGPIA), which inhibits ephrin-B2 binding to EphB4 with an IC 50 value of ~150 µM, was identified by using phage display. Addition of the C-terminal RAW motif to TNYL, based on the sequence alignment of multiple EphB4-binding peptides identified in the same phage display screen, then yielded the TNYL-RAW peptide, which inhibits EphB4 binding with an IC 50 of ~15 nM and has a low nanomolar binding affinity (3840). Thus, the C-terminal RAW sequence is critical for the high-affinity binding of TNYL-RAW to the EphB4 receptor.…”
Section: Introductionmentioning
confidence: 99%